Immune responses to hair dyes containing toluene‐2, 5‐diamine3. (February 2014) - Schmidt, J.D.; Johansen, J.D.; Nielsen, M.M.; Zimersson, E.; Svedman, C.; Bruze, M.; Engkilde, K.; Poulsen, S.S.; Geisler, C.; Bonefeld, C.M.
Summary Background Toluene‐2, 5‐diamine (PTD) is the most frequently used dye in oxidative hair dyes on the Scandinavian market. However, little is known about immune responses to PTD‐containing oxidative hair dyes. Objectives To study immune responses induced by PTD‐containing hair dyes in mice. Methods Immune responses against two different permanent hair dye products containing 1·60% (w/w) and 0·48% (w/w) PTD within the colour gel, and various concentrations of pure PTD were studied. The local inflammatory response was measured by ear swelling and cell infiltration, and T‐ and B‐cell infiltration and proliferation was determined in the draining lymph nodes. Results Concentration‐dependent immune responses were seen to PTD both in the skin and draining lymph nodes. The hair dye containing 1·60% PTD induced strong local inflammation and caused T‐ and B‐cell infiltration and proliferation as well as an increased number of regulatory T cells in the draining lymph nodes. In contrast, the hair dye containing 0·48% PTD induced skin inflammation but only minor responses in the draining lymph nodes. Conclusions Consumer‐available PTD‐containing permanent hair dyes can be potent immune activators inducing both pro‐ and anti‐inflammatory responses. The outcome of the response is dependent on allergen dose, amount of additional allergens and exposure regime.